THE IMPORTANCE OF DISTANCE LEARNING FOR PROFESSIONAL DEVELOPMENT COURSES - Tashkenbaeva, U.A.; Khazratova, G.Sh. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
Introduction. Nowadays, many people use distance-learning programs to study at home. Traditional distance learning models can be useful, but they can be enhanced. These models should be ranged in age and typically possess a variety of academic and professional competencies of the adult learners. The aim of the work is to evaluate and demonstrate the development and significance of the center's courses for regular updating of professional knowledge, skills, and abilities required to ensure the educational process at a high scientific and methodological level, to promote the continuous development of professional and pedagogical skills based on qualification requirements, curricula, and programs in e-Learning environments. This article will also cover tips and techniques for engaging, maintaining, and supporting adult learners in eLearning environments. Conclusion. The system of advanced training and retraining for pedagogical staff operates and grows as part of a single process of updating national pedagogy, ensuring the reform's personnel capacity. The operations of the Industry Centers have progressed to the point where they are able to respond to educational developments in a flexible and timely manner. The end outcome, the last criterion for the activity's excellence, is an improvement in the level of our students' training and education.